(untitled) (Web of Teachers: Inderscience Research, 2023)
This article explores the critical connection between gender equality, corporate leadership, and business success. It investigates how diverse leadership teams, comprising both men and women, contribute to improved decision-making, innovation, and overall company performance. By examining real-world case studies and research, this study highlights the substantial advantages of gender equality in corporate leadership and underscores the need for inclusive practices that empower women to assume key roles in organizations, fostering a more equitable and prosperous business landscape.